2023
DOI: 10.12973/ijem.9.2.321
|View full text |Cite
|
Sign up to set email alerts
|

Game-Based Learning Kit Method in Isometric Transformations: Usability and Effects on Students’ Achievement and Motivation

Abstract: <p style="text-align: justify;">This study focused on the development of teaching aids for the topic of Isometric Transformations for Form 2 students in Malaysia. The first objective was to determine the usability of teaching aids in the isometric transformations kit integrates game-based learning (GBL) Method (KitTI Method) and the second objective was to examine the effectiveness of using the KitTI Method on students’ achievement and motivation. This study was directed by the Design and Development Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Based on conducted studies, it has been found that gamification can increase students' learning motivation, especially for those with low to moderate self-confidence levels in mathematics. Furthermore, motivating tasks, challenges, competitions, rewards and performance improvements can increase students' motivation to learn mathematics (Bouzid et al, 2021;Jagust et al, 2018;Jarrah et al, 2022;Lanuza, 2020;Lanuza et al, 2020;Nasir et al, 2023;Yang and Chen, 2021). By allowing students to select their own challenges and rewards, gamification also helps to personalise maths learning by progressing at their own pace and receiving immediate feedback (Bouzid et al, 2021;Hamid et al, 2022;Hernandez-Nieto and Martinez, 2019;Jarrah et al, 2022;Lanuza, 2020).…”
Section: What Are the Aspects Of The Effectiveness Of Gamification In...mentioning
confidence: 99%
“…Based on conducted studies, it has been found that gamification can increase students' learning motivation, especially for those with low to moderate self-confidence levels in mathematics. Furthermore, motivating tasks, challenges, competitions, rewards and performance improvements can increase students' motivation to learn mathematics (Bouzid et al, 2021;Jagust et al, 2018;Jarrah et al, 2022;Lanuza, 2020;Lanuza et al, 2020;Nasir et al, 2023;Yang and Chen, 2021). By allowing students to select their own challenges and rewards, gamification also helps to personalise maths learning by progressing at their own pace and receiving immediate feedback (Bouzid et al, 2021;Hamid et al, 2022;Hernandez-Nieto and Martinez, 2019;Jarrah et al, 2022;Lanuza, 2020).…”
Section: What Are the Aspects Of The Effectiveness Of Gamification In...mentioning
confidence: 99%
“…Therefore, guided inquiry was chosen as a practical learning model for improving scientific literacy skills because it allows students to be actively involved in the science learning process, develop a deep understanding, and develop the critical and analytical thinking skills needed to understand and apply science. According to research by Nasir et al (2023), scientific literacy significantly influences students' academic achievement at various levels of education.…”
Section: Introductionmentioning
confidence: 99%